Loan - Loss Provisions in Indian Banks : An Appraisal of Institutional Attributes - Pillai, K. R.; Mathew, Linsy (Indian Journal of Finance, 2017)
The financial systems of a nation, being the lifeline of its economy, are expected to have ample preparation to confront and mitigate any shock inherent in a market - driven business. Loan - loss provisioning is a systematic way of handling risks rationally, signaling managerial prudence. Banks across the globe follow a dynamic provision policy. Sometimes, a well - designed policy is not enough to safeguard the interests of all the stakeholders. One such prominent and time - honored modus operandi to face contingencies is the rate of provisioning to be set aside annually to meet any contingencies. The proposed study attempted to report the chronological trend in provision in Indian banks in the latest decade. Data for the study were collected from CMIE online database. Bank size and nature of ownership were considered to be the predictors of provision. The findings of our study revealed that the size of the banks influenced the rate of provisions set aside. The study also revealed a clear distinction among the banks ranked high on the basis of size than medium and low ranked banks. We also recognized the global economic downturn as an incontestable constituent to increase the percentage of provisions across all the sectors of the financial industry.